2006
DOI: 10.1055/s-2006-944971
|View full text |Cite
|
Sign up to set email alerts
|

Is blood the ideal submucosal cushioning agent? A comparative study in a porcine model

Abstract: Blood produces the most durable cushion compared with standard agents, also having the advantages of being readily available and without cost. Albumin 25 % provides as durable a cushion as hydroxypropyl methylcellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Furthermore, in the event of excessive infiltration, the advantage of more permanent lifting becomes an obstacle to endoscopic resection. Thus, if the time of dissipation in blood is much higher that HPMC, as reported by Giday et al,8 the risk of not being able to recover from an excessive injection increases exponentially.…”
Section: Dear Editormentioning
confidence: 90%
“…Furthermore, in the event of excessive infiltration, the advantage of more permanent lifting becomes an obstacle to endoscopic resection. Thus, if the time of dissipation in blood is much higher that HPMC, as reported by Giday et al,8 the risk of not being able to recover from an excessive injection increases exponentially.…”
Section: Dear Editormentioning
confidence: 90%
“…These include Sodium Hyaluronate (SH), Glycerol, Fibrinogen mixture, autologous blood, hypertonic saline solution, and hypertonic glucose to prolong submucosal fluid cushion to enable endoscopic resection of larger neoplastic lesions en bloc. [10][11][12][13][14][15] Of these, hydroxypropyl methylcellulose (HPMC) used commonly to maintain anterior chamber configuration of the eye during surgery has been reported as an effective submucosal cushion in animal models. [16][17][18][19] Feitoza et al 20 first reported use 0.83% HPMC as an submucosal fluid cushion in the pig esophagus.…”
Section: Methodsmentioning
confidence: 99%
“…11 Fibrinogen mixtures, hydroxypropyl methylcellulose, blood, and albumin are other alternatives that create a long-lasting submucosal fluid cushion with minimal tissue reaction. [14][15][16][17] However, by increasing the osmolarity of the solutions, potential tissue damage may occur that may affect specimen quality and healing of the resection site. 12 The fundamental difference between EMR and ESD is the intent to resect the lesion in as few pieces as possible by EMR and in 1 piece by ESD.…”
Section: Capsule Summarymentioning
confidence: 99%